2009
DOI: 10.3171/2008.12.peds08206
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial vasospasm with subsequent stroke after traumatic subarachnoid hemorrhage in a 22-month-old child

Abstract: Clinical and radiographic evidence of subarachnoid hemorrhage (SAH)-related vasospasm is rare in children and has not been reported in infants. In this report the authors present the case of a 22-month-old child who developed clinically symptomatic, radiographically identifiable vasospasm after traumatic SAH. To the authors' knowledge, this is the first report of vasospasm associated with SAH in a child this young. This 22-month-old boy fell and had a dense SAH. He had a history of surgically corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Some patients may benefit from triple-H therapy-hypertension, hypervolemia, and hemodilution-to reduce the risk of vasospasm (after aneurysm treatment). 484,485 The value of using calcium channel blocking agents (eg, nimodipine) in children is unknown.…”
Section: Aneurysmsmentioning
confidence: 99%
“…Some patients may benefit from triple-H therapy-hypertension, hypervolemia, and hemodilution-to reduce the risk of vasospasm (after aneurysm treatment). 484,485 The value of using calcium channel blocking agents (eg, nimodipine) in children is unknown.…”
Section: Aneurysmsmentioning
confidence: 99%
“…7,10,11,15,24,25 While it has been suggested that the presentation of SAH is similar in adult and pediatric patients, 23 specific data regarding the outcomes and management of SAH in the pediatric population remain limited. 31 Risk stratification of pediatric patients with tSAH could allow for the identification of those at low risk for neuroworsening, preventing potentially unnecessary ICU admissions with attendant associated interventions, limiting additional exposure to ionizing radiation and administration of anesthetic agents, and improving overall healthcare efficiencies. In this paper we present the clinical course and neurological outcomes of 51 consecutive pediatric patients with isolated tSAH and mild TBI (GCS score [13][14][15] identified in a prospectively collected database of 10,395 pediatric trauma patients admitted over a 10-year period.…”
mentioning
confidence: 99%
“…There is only 1 report about a child with middle cerebral artery cortical infarction caused by vasospasm. 2 We describe the case of a 4-year-old boy who experienced right hemiparesis and motor aphasia due to a striatocapsular infarction after a traumatic subarachnoid hemorrhage.…”
mentioning
confidence: 99%
“…There is only 1 report about a child with middle cerebral artery cortical infarction caused by vasospasm. 2…”
mentioning
confidence: 99%